Ответы и объяснения

2012-11-27T12:28:44+04:00

10x²+19x-2=(10x-1)(x+2)=10x²+20x-x-2=10x²+19x-2

0,5(x-6)(x-5)=0,5x²-5,5x+15=(0,5x-3)(x-5)=0,5x²-2,5x-3x+15=0,5x²-5,5x+15

2012-11-27T12:34:54+04:00

10х²+19х-2=10(х-0,1)(х+2)

Есть формула:

ax^2+bx+c=a(x-x_1)(x-x_2)

Найдем корни:

10х²+19х-2=0

d=b^2-4ac=361-4*10*(-2)=441   √441=21

x1=-2, x2=0,1

Подставим в формулу:

a(x-x_1)(x-x_2)=10(x-0,1)(x-(-2))=10(x-0,1)(x+2)

 

0,5х²-5,5х+15=0,5(х-6)(х-5)

Найдем корни:

d=b^2-4ac=30,25-4*0,5*15=0,25     √0,25=0,5

x1=5, x2=6

Подставим в формулу:

a(x-x_1)(x-x_2)=0,5(x-(-5,5)(x-15)=


0,5(x+5,5)(x-15)